LIQUIDITY AND SOLVENCY IN THE CONTEXT OF FINANCIAL MANAGEMENT OF ENTERPRISE ACTIVITIES - LOPATOVSKA, OKSANA; GAEVSKA, O. (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considers the theory and methods of assessing the liquidity and solvency of the enterprise through the prism of financial management, which results in the interaction of all elements of financial relations of the enterprise, characterized by a system of indicators, reflecting the availability, allocation and use of financial resources.The interpretation of the economic category "liquidity and solvency management" of the enterprise is studied, namely the authors note that this is the process of developing and making effective management decisions to fulfill business obligations in full and on time due to available means of payment to ensuring stable development of the business entity in the current and future period. The purpose and main tasks of liquidity and solvency management of the enterprise are determined. The main stages of the process of liquidity and solvency management of business entities, as well as the main stages of their analysis.The authors noted that the formation of liquidity and solvency management policy should be based on the following basic principles of financial management: systematic, planned, focused, strategic, variability.The content of strategies for financing current assets is singled out and characterized: ideal; aggressive; conservative; compromise. When choosing a strategy for financing current assets, it is necessary to focus on the desired relationship between the level of profitability and the level of risk of loss of solvency of the enterprise, which is estimated by the required amount of working capital. For effective solvency management, it is necessary to determine which activities and which elements of assets or liabilities have contributed to the growth or reduction of cash, current assets, working capital and working capital and to what extent. At the same time, the assessment of the solvency of the enterprise should focus primarily on the study and analysis of the causes of financial difficulties of the enterprise.The authors noted that liquidity and solvency management is an important component of financial management and the implementation of effective liquidity and solvency management is the basis for further development of enterprises, which in turn will affect their investment attractiveness and competitiveness.
Keywords: financial condition; liquidity; solvency; assets; capital; liabilities; management decisions; financial management